Pengaruh Penerapan Model Pembelajaran Discovery Learning Berbasis Multimedia Video Animaker Terhadap Hasil Belajar Siswa Di SD Negeri 6 Tambun - Hartati H. Tanaiyo; Rudini, Moh; Ummah BK, Muh Khaerul; Ikbal, Ikbal (Tolis Ilmiah : Jurnal Penelitian, 2025)
The problem in this study is the low learning outcomes of students of SD Negeri 6 Tambun in Indonesian subjects, especially in the reading aspect, the less interesting learning model is the main trigger for this. In tackling this, the author conducted a study by applying a multimedia video animaker-based discovery learning model in learning activities. The purpose of this study was to analyze whether there was an effect of the application of the multimedia video Animaker-based Discovery Learning learning model on the Indonesian language learning outcomes of fourth-grade students at SD Negeri 6 Tambun. This study is a quantitative study with a Pre-Experimental design (Pretest-Postest Interaction Group Comparison). The instruments in this study were observation and learning outcome tests with a sample of 22 students, which used a purposive sampling technique in sampling. The data analysis technique used the Wilcoxon Signed Ranks test. The results showed that the probability value was 0.003 which means <0.05, so it can be concluded that H0 is rejected and Ha is accepted. The positive implications of the results of implementing this model with integrated media, teachers can consider integrating technology and multimedia in their teaching strategies to increase student engagement and understanding. Keywords: Animaker, Discovery Learning, Learning Outcomes